A secure Internet of Things medical information sharing and emergency notification system based on nonrepudiation mechanism. Issue 5 (27th March 2020) - Chen, Chin‐Ling; Yang, Tsai‐Tung; Deng, Yong‐Yuan; Chen, Chi‐Hua
Abstract: As the network technologies have rapidly developed in recent years, many Internet of Things (IoT) based services and applications have walked into our daily lives; one of these is the medical information system. In the early days, medical information was recorded and stored in article form. It contains a patient identity background, past medical history, and records of medical payment. With the development of medical technology, medical information is now stored and transmitted electronically. Medical information may be a person's most private information, but due to network operation errors or hacking attacks, there has been a crisis of large‐scale leakage of these personal privacy data in the past. In any cases, how to protect this medical information and ensure the privacy of patients has become a topic worthy of research. Therefore, many kinds of literature discussed how to improve medical information systems. In addition, how to effectively treat patients when accidents happen is also a topic worthy of research. Therefore, combined with IoT technologies and medical devices, it has been opened a whole new future for medical information system. This study focuses on security and privacy issues to design a security scheme for healthcare environments when a person encountered physical emergency. Mobile devices and cloud computing are combined into the proposed platform. The proposed scheme can defend against impersonation attack, man‐in‐middle attack, and replay attack. The modal logic is used to verify the proposed scheme. By using digital signature and SVO logic mechanism, the proposed scheme is proven with nonrepudiation. Abstract : The architecture of the information extension in case of emergency.